One Ring to Fight Them All: The Sulfazecin Story. Issue 1 (19th January 2017) - Braga, Daniel; Lackner, Gerald
Abstract : In this issue of Cell Chemical Biology, Li et al. (2017) report on the biosynthesis of the monobactam sulfazecin by Pseudomonas acidophila and hypothesize a novel mechanism of β-lactam ring formation. As monobactam antibiotics are unaffected by some emerging resistance mechanisms (particularly metallo-β-lactamases), this discovery opens prospects to engineer β-lactam antibiotics against multi-drug resistant pathogens. Abstract : In this issue of Cell Chemical Biology, Li et al. (2017) report on the biosynthesis of the monobactam sulfazecin by Pseudomonas acidophila and hypothesize a novel mechanism of β-lactam ring formation. As monobactams antibiotics are unaffected by some emerging resistance mechanisms (particularly metallo-β-lactamases), this discovery opens prospects to engineer β-lactam antibiotics against multi-drug resistant pathogens.